Haptic Object Recognition is View-Independent in Early Blind but not Sighted People. (March 2016) - Occelli, Valeria; Lacey, Simon; Stephens, Careese; John, Thomas; Sathian, K.
Object recognition, whether visual or haptic, is impaired in sighted people when objects are rotated between learning and test, relative to an unrotated condition, that is, recognition is view-dependent. Loss of vision early in life results in greater reliance on haptic perception for object identification compared with the sighted. Therefore, we hypothesized that early blind people may be more adept at recognizing objects despite spatial transformations. To test this hypothesis, we compared early blind and sighted control participants on a haptic object recognition task. Participants studied pairs of unfamiliar three-dimensional objects and performed a two-alternative forced-choice identification task, with the learned objects presented both unrotated and rotated 180° about the y -axis. Rotation impaired the recognition accuracy of sighted, but not blind, participants. We propose that, consistent with our hypothesis, haptic view-independence in the early blind reflects their greater experience with haptic object perception.